Dietary Diversity Among U.S. Infants and Toddlers: Associations With Caregiver Sociodemographic Characteristics. (14th June 2022) - Lawless, Megan; Shapiro, Allison; Johnson, Susan
Abstract: Objectives: The introduction to a variety of foods during the first two years of life is recommended to ensure adequate intake of essential nutrients required for optimal growth and development. The purpose of this study was to assess dietary diversity among children 4–26 months and to identify associations between caregiver sociodemographic characteristics and child dietary diversity. Methods: Caregivers, recruited via Qualtrics panels, reported on how often foods (n = 57) were offered to their child in the prior month using a food frequency questionnaire designed to assess usual intakes of infant/toddler foods. Foods were grouped (vegetables, fruits, grains, meat and meat alternatives, snacks, sweets, and dairy) and summed into a 7-point dietary diversity score (DDS). Tertiles of dietary diversity were used to classify children by age into low, average, and high diversity. Ordinal logistic regression tested the association between caregiver sociodemographic factors (age, race/ethnicity, household income, partner status, household size) and tertile of child DDS. Results: Caregivers (n = 344; 70.3% female; M ± SD age 31.5 ± 6.3 y), identified as White (73%), and had attended at least some college (74%). The average DDS for the sample was 4.2 ± 2.35. Among infants (< 12 months; n = 150), 50.8% received breastmilk, 39% consumed 0–2 food groups and 42.0% consumed ≥ 5 food groups (DDS 3.6 ± 2.5). Among toddlers (>12 months; n = 194), 24.8% received breastmilk, 18% consumed 0–2 food groups and 62% consumed ≥ 5 food groups (DDS 4.7 ± 2.1). A Pearson's Chi-Squared test revealed a significant association between breastfeeding status and DDS (c 2 (2) = 8.272, P < 0.05). 23% of children who were receiving breastmilk were classified as low DDS compared with 35% of children not receiving breastmilk. Children from households with ≥ 5 members had 2.7 (95% CI, 1.44 to 4.95) times the odds of high DDS than children from households with ≤ 2 members (P < 0.01). No other caregiver sociodemographic factors were significantly associated with child DDS. Conclusions: Caregiver sociodemographic factors, other than household size, were not related to children's DDS. Given the importance of dietary variety on nutrition adequacy, future work should consider other factors that might influence DDS among infants and toddlers. Funding Sources: This project was unfunded.